The evaluation of the running speed and agility performance in professional and amateur soccer players - Kaplan, T.; Erkmen, N.; Taskin, H. (The Journal of Strength and Conditioning Research, 2009)
The professional and amateur soccer players were tested to determine the running speed and agility performance by playing positions. The sample included 108 professional male soccer players at the national level and 79 amateur male soccer players at a regional level on teams from 10 clubs in Turkey. The study involved the players being assessed by the 10- × 5-m shuttle run test ( 10 × 5 SRT) on a soccer field in a soccer season. The difference between the mean scores of the professional and amateur players is significant. Differences between mean scores according to playing positions of soccer players are not significant. In conclusion, professional soccer players' running speed and agility performances are higher than amateur soccer players. In addition, these results indicate that all soccer players have the same running speed and agility performance in accordance with their different playing positions. Coaches should consider individual training programs based on the positional role of soccer players.